Working class in Turkey during the World War II period: between social policies and everyday experiences - Nacar, Can. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2004., 2004)
Even though Turkey did not become a part of the conflict in the World War II, the economic and social life of the country was heavily affected by the war conditions. The wartime scarcities, high levels of inflation, and government regulations as regards to economy and work life enabled various actors, such as manufacturers, importers, and large and middle landowners to accumulate a substantial amount of capital. The capital accumulation that occurred during the war years was one of the important factors, which made the private enterprises' active role in the economic life in the post-war era possible. On the other hand, large segments of the society were hard hit by the war conditions. Amongst them, this thesis focuses on the everyday experiences of the working class in the urban areas. Although in most cases working people worked long hours in unhealthy environments, they faced great difficulties in meeting their basic needs. However, they did not remain mere objects of the social circumstances. Resorting to various means, they attempted to challenge the social relation imposed on them and improve their conditions. The activities and demands that were brought on to the agenda for the fulfillment of these goals became a critical factor in the formation of a welfare regime that had at its center the labor
Keywords: Working class.; World War, 1939-1945 -- Turkey.